2017
DOI: 10.1002/ente.201700561
|View full text |Cite
|
Sign up to set email alerts
|

CH3NH3Br Additive for Enhanced Photovoltaic Performance and Air Stability of Planar Perovskite Solar Cells prepared by Two‐Step Dipping Method

Abstract: The biggest challenge for the pursuit of potentially available perovskite solar cells (PSCs) is to achieve both high power conversion efficiency and good long‐term stability. Here we report a facile CH3NH3Br (MABr) additive route to achieve the aim. We demonstrate that the application of MABr additive can greatly improve the quality of the perovskite film by diminishing the number of small crystal grains to form large ones, which can substantially decrease grain boundaries and enable direct connection of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A chemical additive or photoactivation fills these anion vacancies. In the former case, halide ions from halogen gases, [ 8 ] halogen compounds AX [ 9 ] ( A = MA/FA/Cs/Na/K and X = Cl/Br/I), organic pseudohalides, [ 10 ] or ligands [ 11 ] fill the vacancies. In the latter case, the so‐called light soaking effect, molecules like oxygen improve the PL of LHPs by photoinduced defect passivation.…”
Section: Introductionmentioning
confidence: 99%
“…A chemical additive or photoactivation fills these anion vacancies. In the former case, halide ions from halogen gases, [ 8 ] halogen compounds AX [ 9 ] ( A = MA/FA/Cs/Na/K and X = Cl/Br/I), organic pseudohalides, [ 10 ] or ligands [ 11 ] fill the vacancies. In the latter case, the so‐called light soaking effect, molecules like oxygen improve the PL of LHPs by photoinduced defect passivation.…”
Section: Introductionmentioning
confidence: 99%
“…The time-resolved PL (TRPL) spectra of the corresponding films are shown in Figure c. The parameters sorted by exponential fitting are listed in Table S1 (Supporting Information). , Compared with the carrier lifetime of the CsPbIBr 2 film (∼0.94 ns), the CsPbIBr 2 /QS film shows a longer carrier lifetime of 2.40 ns. The results of the enhanced PL intensity and PL decay lifetime show that QS passivation can effectively promote charge extraction at the interface and reduce the nonradiative recombination of photogenerated carriers in the CsPbIBr 2 /QS film. , …”
Section: Resultsmentioning
confidence: 99%
“…Here, we introduce a two-step method to fabricate FAPbBr 3 on a SnO 2 electron transport layer. By adding methylammonium bromide (MABr) in the precursor solution, we found that the quality of the perovskite film is improved, and it can also help us to improve the deficiency of Br, making the Br/Pb ratio closer to three in the perovskite film. Methylammonium chloride (MACl) has been reported to enable growth of high-quality perovskite films based on FAPbI 3 .…”
Section: Introductionmentioning
confidence: 99%